Mask Mandates and Dilemmas of Disability Difference - Mintz, Kevin (The Hastings Center report, 2022)
A number of recent legal cases in the United States have considered both disability-based exceptions to Covid-19-related mask mandates and disability-based claims to stronger masking rules in states restricting the abilities of local governments to enforce mask mandates. We argue that a proper legal and ethical analysis of such cases requires understanding the distinction between disability accommodations and disability modifications. Disability accommodations are individualized adjustments that enable qualified individuals to perform jobs or achieve access on terms comparable to those experienced by others. Disability modifications are programmatic changes to structures or policies that increase accessibility. We contend that in the context of mask mandates, modifications rather than accommodations are ethically desirable because modification-oriented policies promote disability access in a way that treats all individuals fairly, avoiding the risk of promoting misinformation and uncertainty about the health benefits of masking.